1993
DOI: 10.7326/0003-4819-118-12-199306150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Association between Bovine Collagen Dermal Implants and a Dermatomyositis or a Polymyositis-like Syndrome

Abstract: Because these data suggest that an immunologic response to bovine type I or type III collagen or both caused this dermatomyositis or polymyositis-like syndrome, the risks versus benefits for the cosmetic use of collagen implants should be reassessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 0 publications
0
32
1
1
Order By: Relevance
“…Between 1 and 9.8% of the negative patients may, however, show evidence of hypersensitivity reactions after collagen injection, encompassing edema, erythema, skin induration, and local pruritus [13]. Biopsy specimens from injection sites usually show typical foreignbody granulomas [13,14]. In addition, systemic adverse reactions have also been described [13,15,16,17,18].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Between 1 and 9.8% of the negative patients may, however, show evidence of hypersensitivity reactions after collagen injection, encompassing edema, erythema, skin induration, and local pruritus [13]. Biopsy specimens from injection sites usually show typical foreignbody granulomas [13,14]. In addition, systemic adverse reactions have also been described [13,15,16,17,18].…”
Section: Discussionmentioning
confidence: 97%
“…Positive tests arise in approximately 2.5 to 4% of persons and result in an implant material contraindication [13]. Between 1 and 9.8% of the negative patients may, however, show evidence of hypersensitivity reactions after collagen injection, encompassing edema, erythema, skin induration, and local pruritus [13]. Biopsy specimens from injection sites usually show typical foreignbody granulomas [13,14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cukier et al [29] have reported that the incidence of DM or PM was statistically increased among collagen-treated patients (8 patients with DM and 1 patient with PM among approximately 345,000 patients receiving injectable bovine collagen from July 1980 to June 1988) compared with the expected incidence in the general population.…”
Section: Autoimmune Diseases and Injectable Collagenmentioning
confidence: 99%
“…Although it is not prone to migration or granuloma formation, GAX-collagen fails to conserve its volume over time, resulting in the need for periodic retreatment [12]. In addition, its administration has been implicated in acute hypersensitivity reactions and in the sporadic development of connective-tissue diseases posttherapy [10].…”
mentioning
confidence: 99%